Analisis Faktor-Faktor yang Memengaruhi Output Sektor Industri Pengolahan di Provinsi Jawa Tengah - Selviana Raharjo; Dedi Budiman; Sahara Sahara (Diponegoro University, 2021)
Industrial manufacturing sektor has the biggest contribution to regional economic development of Central Java Province but in the last few years the output of industrial sector experienced a slowing down growth. This industrial manufacturing sector is influenced by many variables. This study identified the effect of macroeconomic variables on industrial manufacturing sector performance in Central Java Province. Macroeconomic variables used in this study were export, import, domestic investment, foreign direct investment, province minimum wage, labour, road and electricity infrastructure, inflation and dummy regional outonom. The methods used to analyze this study were vector error correction model (VECM). A forecast error variance decomposotion (FEVD) test also were used to show the contributions of each macroeconomic variables to the output of manufacture sector. The result of VECM equation shows that in the long-term both domestic investment (PMDN) and foreign investment (PMA) significantly influenced industrial manufacture output. Meanwhile FEVD test shows export, output growth, foreign investment and labour has the bigest composition on explaining manufacturing fluctuations in long-term.